An unheeded plea - LEE, Sean Teck Hao (Institutional Knowledge at Singapore Management University, 2019)
This brief piece of creative writing presents a case of an elderly woman being treated for atherosclerosis via angioplasty. What was particularly unforgettable to the author was that the elderly woman repeatedly remarked that she needed to use the bathroom. Sadly, complications arose in the supposedly minor and low-risk procedure, and she was never able to use the bathroom as she had hoped to.On the operating table, a woman above her 80s laid still. She whimpered as the doctor threaded catheters toward her heart. "I need to pee," she weakly muttered. "It'll be done soon," a nurse replied. "I need to pee!" she exclaimed again. Her plea went unheeded, before a flat tone of death soon sounded.